The social history of three Western Cape thermal mineral springs resorts and their influence on the development of the health and wellness tourism industry in South Africa - Van Wyk, Dane (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2013.